Experiences of mothers receiving donated embryos - Mitra Zandi; Sahar Dabaghi; Atefe Salimi Akinabadi; Narges Bagheri-Lankarani; Reza Omani-Samani; Mostafa Abdolmaleki (Wolters Kluwer Medknow Publications, 2023)
Background: The efficacy of Assisted Reproductive Techniques (ARTs) or technologies used to treat infertile couples has been approved. One such technique is embryo donation. However, there is insufficient knowledge of the experiences of mothers receiving donated embryos. Thus, the present study was conducted with the aim to determine the experiences of mothers receiving donated embryos. Materials and Methods: This qualitative conventional content analysis study was conducted in 2018 for 8 months (from February to September). The research setting was Royan Institute. Mothers receiving donated embryos were selected from among those who were pregnant or were at the postpartum stage using the purposive sampling method. A total of 15 interviews were performed with 13 participants. The qualitative data were collected using deep unstructured interviews and analyzed using the Graneheim and Lundman (2004) method in (version 10; VERBI GmbH, Berlin, Germany) software. Results: Data analysis resulted in 412 open codes that were then categorized into 7 main categories and their subcategories. The main categories were as follows: sociocultural constraint, feeling of insecurity in personal and family identity, protection of personal and family identity, confounded support, pressure and hardship, and achieving relative tranquility. Conclusions: The results of this study showed that the mothers who underwent embryo donation experienced feelings of insecurity regarding both individual and family identities, were confronted with sociocultural difficulties, and faced various pressures. It is suggested that future care plans be focused on the identity crisis of these families and the children resulting from these methods, and that future plans balance the socioeconomic pressures resulting from the use of these methods.